Validation of Spanish version of 15‐item myasthenia gravis quality‐of‐life questionnaire. (15th June 2021) - Contreras, Juan Pablo; Salinas, Rodrigo; Vidal, Carolina; Hoffmeister, Lorena; Wolfe, Gil I.; Cea, Gabriel
Abstract: Objectives: The aim of this study was to achieve the translation and cross‐cultural adaptation of the MG‐QOL15R questionnaire into Spanish and the analysis of its psychometric properties. Materials and Methods: We recruited patients with MG, ≥18 years old, whose mother tongue was Spanish. After the translation and cross‐cultural adaptation of the MG‐QOL15‐R, the following tests were performed: internal consistency using the Cronbach‐α coefficient and corrected item‐total correlations; reproducibility with a test‐retest analysis using intraclass correlation coefficients; and concurrent validity using Spearman's correlation coefficient of the Spanish language MG‐QOL15R‐S, Myasthenia Gravis Activity of Daily Living (MG‐ADL) and Quantitative Myasthenia Gravis (QMG) scores. As an approximation to construct validity, the nonparametric Mann‐Whitney U test was performed between MG‐QOL15R‐S scores according to the Myasthenia Gravis Foundation of America classification. Results: A total of 83 MG patients were enrolled, mean age 48.19 ± 17.25 years; 58 (69.9%) were women. The mean MG‐QOL15R‐S score was 11.3 ± 7.1. Cronbach‐α coefficient was 0.92. Item‐total correlation ranged between 0.43 and 0.75. Intraclass correlation coefficient was 0.80. The Spearman correlation coefficient was 0.637 ( p ‐value < .001) for MG‐ADL and 0.487 ( p ‐value < .001) for QMG. Mann‐Whitney U tests of the mean MG‐QOL15R‐S scores were significantly different according to the clinical severity ( p ‐value < .001). Conclusions: The Spanish version of the MG‐QOL15R is a valid and reliable instrument and potentially useful for measuring health‐related quality of life in Spanish‐speaking MG patients.